2013
DOI: 10.1093/deafed/ens069
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Tense Marking in English-Speaking Children with Cochlear Implants: A Longitudinal Study

Abstract: This study investigated the development of tense markers (e.g., past tense -ed) in children with cochlear implants (CIs) over a 3-year span. Nine children who received CIs before 30 months of age participated in this study at three, four, and five years postimplantation. Nine typical 3-, 4-, and 5-year- olds served as control groups. All children participated in a story-retell task. Percent correct of tense marking in the task was computed. Within the groups, percent correct of tense marking changed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 41 publications
3
36
0
2
Order By: Relevance
“…(d) Would children with CIs demonstrate different patterns of grammatical errors from their age-matched peers with typical hearing? On the basis of previous studies (Chilosi et al, 2013;Guo et al, 2013;Nicholas & Geers, 2007;Nikolopoulos et al, 2004), we predicted that PGCU would increase over developmental time in children with CIs. We also predicted that children with CIs would produce PGCU at a lower level as compared with their age-matched peers with typical hearing, given the auditory-perceptual and cognitive-processing constraints.…”
Section: The Present Studymentioning
confidence: 97%
See 4 more Smart Citations
“…(d) Would children with CIs demonstrate different patterns of grammatical errors from their age-matched peers with typical hearing? On the basis of previous studies (Chilosi et al, 2013;Guo et al, 2013;Nicholas & Geers, 2007;Nikolopoulos et al, 2004), we predicted that PGCU would increase over developmental time in children with CIs. We also predicted that children with CIs would produce PGCU at a lower level as compared with their age-matched peers with typical hearing, given the auditory-perceptual and cognitive-processing constraints.…”
Section: The Present Studymentioning
confidence: 97%
“…Although some studies (e.g., Guo et al, 2013) have found that English-speaking children with CIs produce more errors in marking verb tense than children with typical hearing, few if any have systematically examined other types of grammatical errors (e.g., argument structure, word order) in this population.…”
Section: Development Of Grammatical Skills In Children With Cis: Evidmentioning
confidence: 99%
See 3 more Smart Citations